Family Functioning and Parent Support Trajectories and Substance Use and Misuse among Minority Urban Adolescents: A Latent Class Growth Analysis. (6th December 2014) - Cordova, David; Heinze, Justin; Mistry, Ritesh; Hsieh, Hsing-Fang; Stoddard, Sarah; Salas-Wright, Christopher P.; Zimmerman, Marc A
<x xml:space="preserve">Abstract</x> We sought to examine latent classes of family functioning and parent support trajectories during high school and whether these trajectories are associated with an increased risk of substance use and misuse among urban youth. A total of 850 adolescents (Mage = 15.1 years) were included in this study, assessed at baseline, 12-, 24-, and 36-months postbaseline, and completed self-report measures on past 30-day alcohol and marijuana use, binge drinking, and measures of family functioning and parent support. Latent class growth analysis revealed that trajectories of high family functioning and parent support are associated with a decreased risk of marijuana use. Findings may be helpful to inform family-based preventive interventions.